Microsoft Outlook 2002 - Shelly, Gary B. (Course Technology, 2002)
Part of the highly successful Shelly Cashman Series, this text offers a clear, step-by-step, screen-by-screen approach to learning the basic skills of Microsoft Outlook 2002. One project demonstrates how to create calendars, schedule appointments, set up address books, and send e-mail